Concentration camps : a short history - Stone, Dan (Oxford University Press, 2017)
In this book, Dan Stone gives a global history of concentration camps, and shows that it is not only 'mad dictators' who have set up camps, but instead all varieties of states, including liberal democracies, that have made use of them. Setting concentration camps against the longer history of incarceration, he explains how the ability of the modern state to control populations led to the creation of this extreme institution. Looking at their emergence and spread around the world, Stone argues that concentration camps serve the purpose, from the point of view of the state in crisis, of removing a section of the population that is perceived to be threatening, traitorous, or diseased. Drawing on contemporary accounts of camps, as well as the philosophical literature surrounding them, Stone considers the story camps tell us about the nature of the modern world as well as about specific regimes